2013
DOI: 10.1002/grl.50097
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of 2006 Northern Hemisphere contrail coverage using MODIS data

Abstract: A modified automated contrail detection algorithm (CDA) using five infrared channels available from the Moderate Resolution Imaging Spectrometer onboard the Aqua satellite is used to determine linear contrail coverage over the Northern Hemisphere during 2006. Commercial aircraft flight data are employed to filter false contrail detections by the CDA. The Northern Hemisphere annual mean linear contrail coverage ranges from 0.07% to 0.40% for three different CDA sensitivities. Based on visual analyses, the mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 25 publications
(39 reference statements)
5
58
0
Order By: Relevance
“…The average width obtained here is 7.8 km (standard deviation, 2.0 km). It is possible to compare our findings with the study by Duda et al (2013) where three different masks were implemented to examine contrail coverage. The widths they derived ranged from 3.75 km (most restrictive mask, exclusively linear contrails) to 5.23 km (some contrail cirrus included).…”
Section: Length and Widthmentioning
confidence: 85%
See 1 more Smart Citation
“…The average width obtained here is 7.8 km (standard deviation, 2.0 km). It is possible to compare our findings with the study by Duda et al (2013) where three different masks were implemented to examine contrail coverage. The widths they derived ranged from 3.75 km (most restrictive mask, exclusively linear contrails) to 5.23 km (some contrail cirrus included).…”
Section: Length and Widthmentioning
confidence: 85%
“…It has already been used to study linear contrail coverage on several regions of the Earth: central Europe (Meyer et al, 2002), North America , eastern North Pacific , southern and eastern Asia (Meyer et al, 2007) and the North Atlantic (Graf et al, 2012). A modified version of the algorithm has recently been used by Duda et al (2013); Bedka et al (2013) and Spangenberg et al (2013) to estimate several linear contrail properties in the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…This results in small horizontal coverage but a corresponding thicker optical depth. Cloud fractions given in Table 2 of Chen et al (2012) are, thus, not equivalent to cloud cover published in previous literature, be it simulated (e.g., Frömming et al, 2011) or observed (e.g., Duda et al, 2013) cover. However, we will demonstrate that the grid-box average optical depth and radiative forcing using this method are consistent with other work.…”
Section: Contrail Parameterizationmentioning
confidence: 85%
“…3a) peaks at 1.2% over several oceanic air routes. Just after Using the MODIS results of Duda et al (2013), Bedka et al (2013) found an average contrail temperature of −51.8°C with daytime and nighttime modes at −55° and −47°C, respectively, values that are slightly warmer than those from Iwabuchi et al (2012). Bedka et al (2013) also retrieved mean COD and D E values of 0.208 and 34.4 µm, respectively, with a small seasonal cycle in both.…”
Section: Midnight (mentioning
confidence: 96%
“…For the first time, the AC-CRI program, using satellite data, characterized near-global linear contrail coverage and its optical and radiative properties (T con , D E , and COD) and the corresponding RF. Duda et al (2013) developed an optimized linear contrail detection algorithm (CDA) for application to Moderate Resolution Imaging Spectroradiometer data (MODIS; Barnes et al 1998) and produced the most comprehensive LC observational dataset to date (Fig. 3) by analyzing all Northern Hemisphere MODIS data during 2006.…”
Section: Midnight (mentioning
confidence: 99%